Industrial Revolution 4.0 (IR4.0) Enrichment Program at SMK Gudang Rasau (SEGRA) - Nor Azhar, Ahmad (Faculty of Computer System & Software Engineering, 2019)
One of the IR4.0 hype element is the internet of things (IoT). This element always has a good spotlight in mass media nowadays as one of the futures needed job. This emerging technology will take over most of the human activities, especially in the manufacturing industry. Realizing the importance of early exposure to the youngster, SEGRA had invited Mr Nor Azhar Ahmad from Faculty of Computing, Universiti Malaysia Pahang for in house training.